Innovative development of the road and transport complex: problems and prospects - Iaroslava Levchenko; Illia Dmytriiev (PC TECHNOLOGY CENTER, 2023)
The monograph pays attention to the problems and prospects of innovative development of the road and transport complex. In Ukraine, the road and transport complex is classified as a priority system. And taking into account its key role in the defense of the state, the need to carry out scientific developments and practical recommendations for the development of the road and transport system as a whole is becoming urgent. Factors affecting the transport infrastructure of the area and the economic consequences of their implementation have been systematized, and a system of management of the transport infrastructure has been developed. The stages of formation and implementation of entrepreneurial strategies, which determine the sustainable innovative development of road and railway transport enterprises, have been developed. The methodical approach to the development of the list of indicators of preventive anti-crisis management of the road enterprise has been improved thanks to the comprehensive consideration of the results of the study of the quantitative and qualitative composition of the indicators of the CVP analysis. The personnel management system of the motor vehicle enterprise has been formed on the basis of a holistic approach, and a methodology for assessing the effectiveness of the enterprise's personnel control was proposed, which helps to identify the weakest points in the existing control system. In order to determine the objects of innovative activity, the urgency and timeliness of the application of functional-cost analysis has been proven. In order to achieve an economic and ecological effect in defined strategy improve cars for earthy road construction works. The proposed theoretical, methodological and applied aspects of the development of the road and transport complex are of theoretical and practical interest for scientists, entrepreneurs and state administration bodies.
Keywords: 380; Road and transport system; road transport; railway transport; road construction; transport and logistics services; competences of employees; control; quality of transport services